2020
DOI: 10.25100/cm.v51i2.4327
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and HIV

Abstract: Throughout the COVID-19 pandemic, the main risk factors associated with the progression to severe disease or death have been typically advanced age, diabetes mellitus, obesity, high blood pressure, heart disease, and chronic pneumopathy. Because of their immunosuppression status, persons with HIV were also expected to have a higher susceptibility to infection or a poor clinical evolution. So far, this has not been confirmed to happen, giving way to hypotheses about the role of immunosuppression or the use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…While maintaining suppressed viral load and a normal CD4 T-lymphocyte count likely decreases the risk of severe COVID-19, there is yet to be clear evidence that ART itself prevents the acquisition of SARS-CoV-2 infection or alters the rate of progression to severe disease. 51 , 144 , 195–201 Three observational studies have suggested a potential protective role of tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC) among PWH. 91 , 202 , 203 The last of these adjusted for comorbidities, demographics, country of birth, and education level.…”
Section: Discussionmentioning
confidence: 99%
“…While maintaining suppressed viral load and a normal CD4 T-lymphocyte count likely decreases the risk of severe COVID-19, there is yet to be clear evidence that ART itself prevents the acquisition of SARS-CoV-2 infection or alters the rate of progression to severe disease. 51 , 144 , 195–201 Three observational studies have suggested a potential protective role of tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC) among PWH. 91 , 202 , 203 The last of these adjusted for comorbidities, demographics, country of birth, and education level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are differences between the receptors through which HIV and other pathogenic coronaviruses enter target cells, the ways of assembly, and their encapsulation. In the case of HIV, it does so near the cytoplasmic membrane, and in the case of coronavirus , the process takes place in the endoplasmic reticulum, which may suggest that there is no synergistic or cooperative pathogenesis [ 53 ].…”
Section: Coinfection With Virusmentioning
confidence: 99%
“…Managing COVID-19 directly impacts the local HIV prevention and care landscape, which heavily relies on digital HIV intervention programs ( 5 ). Owing to their immunosuppressed state, PLHIV are presumed to be more susceptible to COVID-19 infection and may experience worse clinical outcomes ( 6 ).…”
Section: Introductionmentioning
confidence: 99%